Direct studies of ligand-receptor interactions and ion channel blocking (Review). - Watts, A (2002)
Small molecules can activate membrane bound receptors to elicit cellular responses and approximately 80% of all such responses are mediated through membranes. Solid state nuclear magnetic resonance (NMR) methods have been developed for the resolution of specifically labelled ligands, designed to report back structural, dynamic and electronic details of the ligand whilst at its site of action. In particular, ion channel blockers, drugs, inhibitors, prosthetic groups and solutes have been studied when at their target site in functionally competent membranes. A blocker of the channel in the anion transporter of erythrocytes (AE1) has been studied to show that considerable motional freedom within the channel site occurs. The activating agonist of the ligand gated ion channel, the nicotinic acetylcholine receptor, is constrained at its site of action and binds through a cation-pi interaction as revealed in the NMR spectra. The footprint for the inhibitor binding site of the digitalis receptor, the Na(+)/K(+)-ATPase has been resolved as well as the molecular conformation of digitalis showing a bent structure whilst at its site of action. For the gastric proton pump, however, a planar conformation is observed for a reversible substituted imidazopyridine. In all cases not only the structure, but also some indications about the electronic interactions of ligand and target have been resolved using these approaches.